Household Transmission of Group A Streptococcus Necrotizing Fasciitis. (3rd August 2022) - Markowitz, Michael; Kwan, Stephanie; Matzon, Jonas L.
Abstract : A healthy 40-year-old woman was diagnosed with necrotizing fasciitis 2 days after her husband's death from the same infectious process. Prompt identification and immediate surgical intervention prevented a similar result in this patient. Additional investigation into both patients' medical records found the inciting organism to be group A streptococcus. Although the exact mechanism of inoculation is unknown, the spread of this infection within a household prompts the question of whether antibiotic prophylaxis should be given among close contacts in future cases of necrotizing fasciitis.